Learning from an equitable, data‐informed response to COVID‐19: Translating knowledge into future action and preparation - Morgen Stanzler; Johanna Figueroa; Andrew F. Beck; Marianne E. McPherson; Steve Miff; Heidi Penix; Jessica Little; Bhargavi Sampath; Pierre Barker; David M. Hartley (Wiley, 2024)
Abstract Introduction The COVID‐19 pandemic revealed numerous barriers to effectively managing public health crises, including difficulties in using publicly available, community‐level data to create learning systems in support of local public health decision responses. Early in the COVID‐19 pandemic, a group of health care partners began meeting to learn from their collective experiences. We identified key tools and processes for using data and learning system structures to drive equitable public health decision making throughout different phases of the pandemic. Methods In fall of 2021, the team developed an initial theory of change directed at achieving herd immunity for COVID‐19. The theoretical drivers were explored qualitatively through a series of nine 45‐min telephonic interviews conducted with 16 public health and community leaders across the United States. Interview responses were analyzed into key themes to inform potential future practices, tools, and systems. In addition to the interviews, partners in Dallas and Cincinnati reflected on their own COVID‐19 experiences. Results Interview responses fell broadly into four themes that contribute to effective, community driven responses to COVID‐19: real‐time, accessible data that are mindful of the tension between community transparency and individual privacy; a continued fostering of public trust; adaptable infrastructures and systems; and creating cohesive community coalitions with shared alignment and goals. These themes and partner experiences helped us revise our preliminary theory of change around the importance of community collaboration and trust building and also helped refine the development of the Community Protection Dashboard tool. Conclusions There was broad agreement amongst public health and community leaders about the key elements of the data and learning systems required to manage public health responses to COVID‐19. These findings may be informative for guiding the use of data and learning in the management of future public health crises or population health initiatives.